Mastering Active Directory - Second Edition - Francis, Dishan (Packt Publishing, 2019)
Become an expert at managing enterprise identity infrastructure by leveraging Active Directory Key Features Explore the new features in Active Directory Domain Service Manage your Active Directory services for Windows Server 2016 effectively Automate administrative tasks in Active Directory using PowerShell Core 6.x Book Description Active Directory (AD) is a centralized and standardized system that automates networked management of user data, security, and distributed resources and enables inter-operation with other directories. This book will first help you brush up on the AD architecture and fundamentals, before guiding you through core components, such as sites, trust relationships, objects, and attributes. You will then explore AD schemas, LDAP, RMS, and security best practices to understand objects and components and how they can be used effectively. Next, the book will provide extensive coverage of AD Domain Services and Federation Services for Windows Server 2016, and help you explore their new features. Furthermore, you will learn to manage your identity infrastructure for a hybrid cloud setup. All this will help you design, plan, deploy, manage operations, and troubleshoot your enterprise identity infrastructure in a secure and effective manner. You'll later discover Azure AD Module, and learn to automate administrative tasks using PowerShell cmdlets. All along, this updated second edition will cover content based on the latest version of Active Directory, PowerShell 5.1 and LDAP. By the end of this book, you'll be well versed with best practices and troubleshooting techniques for improving security and performance in identity infrastructures. What you will learn Design your Hybrid AD environment by evaluating business and technology requirements Protect sensitive data in a hybrid environment using Azure Information Protection Explore advanced functionalities of the schema Learn about Flexible Single Master Operation (FSMO) roles and their placement Install and migrate Active Directory from older versions to Active Directory 2016 Control users, groups, and devices effectively Design your OU structure in the most effective way Integrate Azure AD with Active Directory Domain Services for a hybrid setup Who this book is for If you are an Active Directory administrator, system administrator, or network professional who has basic knowledge of Active Directory and is looking to become an expert in this topic, this book is for you.